Reimagining Early Childhood Education in Southern Africa: Transforming Fragmented Curriculum through Cultural Pedagogy - Pinias Chikuvadze; Christopher Mutseekwa; Claretah Makuvire; Joseph Zuva (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: This paper centres on cultural pedagogy and its influence on transforming fragmented approaches into holistic, inclusive frameworks that nurture identity, community values, and lifelong learning. Aims and scope of paper: This study aims to transform fragmented Early Childhood Education (ECE) curricula in Southern Africa by embedding cultural pedagogy that nurtures holistic child development and strengthens cultural identity. It focuses on examining existing frameworks to identify gaps in cultural relevance while exploring indigenous knowledge systems, storytelling, play, and community-based practices as tools for curriculum transformation. Finally, the study sought to propose an integrated model that fosters identity formation, social cohesion, and lays strong foundations for lifelong learning. Methods: A systematic review approach guided by the PRISMA framework was employed to cross-examine 79 sources purposively selected from targeted databases (Scopus, Web of Science, DOAJ, AJOL, and Scielo, SA). Thematic analysis was employed to identify trends and gaps linked to cultural pedagogy and curriculum transformation in ECE across Southern Africa. Results: Based on the results, it was drawn that Ubuntugogy and chat theory formed the theoretical underpinning of cultural pedagogy in the ECE space. It was also revealed that curriculum fragmentation and pedagogical marginalisation were influenced by the historical, structural, and institutional factors. The results acknowledged the significance of language, storytelling, music, and play in nurturing culturally grounded ECE. In addition, the reviewed sources argued for inclusive curriculum frameworks, integration of cultural pedagogy into ECE policies, and a paradigm shift towards child-centred and community-based learning. Lastly, the selected sources emphasised the challenges and opportunities in redefining fragmented ECE curriculum across Southern Africa. Contribution: This study contributes by providing a culturally responsive framework that addresses fragmented early childhood curricula in Southern Africa. It offers practical insights for educators, policymakers, and communities to design inclusive programmes that strengthen identity, social cohesion, and lifelong learning foundations.